Some Characteristics of Air Distribution at Application of Linear Crevice Diffuser - Yaroslav Chemerynskyi; Orest Voznyak (Energy Engineering and Control Systems, 2025)
The organization of air distribution is one of the key aspects of creating a comfortable and healthy indoor climate. The effectiveness of this process affects not only temperature and humidity, but also overall air quality, which directly impacts people's well-being. To ensure optimal air distribution, a variety of ventilation devices are used, including grilles and diffusers, which differ in design and technical characteristics. Recently, louvered linear diffusers have gained considerable popularity, combining high functionality with modern design. These devices are in line with current architectural and design trends, where special attention is paid to aesthetics, integration into the interior and small details. With an innovative design with multiple parallel air outlets, louvered linear diffusers create unique airflows that actively interact with each other, contributing to turbulence and ensuring even air distribution in the room. This approach not only increases the efficiency of ventilation systems, but also creates comfortable conditions for staying, minimizing drafts and temperature fluctuations.